Guest Service Ambassador Performance: Post-Crisis Adaptation - Sari, Ni Made Dewi Nirmala; Adi, Ida Ayu Sri Puspa; Indrayani, I Gusti Ayu Putu Wita (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to analyze the performance of guest service ambassadors at Hotel XYZ in the new normal era. The research method used is descriptive qualitative. The techniques used to collect data include interviews with front office managers, and also observations of guest service employees. Other data that supports this study comes from literature, journal references, books, and articles about the front office department and employee performance. This study uses the Performance theory which contains four indicators to measure performance, namely quality, quantity, cooperation, and responsibility. From the results of the study, it can be seen that performance still needs to be improved because there are indicators that are not optimal, namely the quantity indicator. The suggestion that can be given is that training should be held such as communication exercises for the guest service Ambassador section in terms of upselling.